2021
DOI: 10.21608/amj.2021.178669
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Administration of Ascorbic Acid in Prevention of Contrast Induced Nephropathy in Patients With Renal Impairment Undergoing Coronary Intervention

Abstract: Background: Contrast-induced nephropathy is a potentially avoidable complication caused during procedures involving the use of radiographic contrast media. All subjects, especially the high-risk ones, should be subjected to available preventive protocols prior to and after such procedures. Objective:To evaluate the role of a hydration protocol involving the use of ascorbic acid plus the conventional sodium chloride hydration protocol N acetyl cysteine. Patients and methods:The current study was conducted on 86… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…NAC positive on humans [53][54][55][56][57][58]60], meta-analyses [59,61,71] no results on humans [62][63][64][65][66][67], meta-analyses [68,69,72] Glutathione no results on humans [78][79][80] Vitamin C positive on humans [96][97][98], meta-analyses [94,95] no results on humans [99][100][101][102][103][104] Vitamin E positive on humans, meta-analyses [113,114] no results on humans [115,116] Bilirubin/HO-1 positive (expected)…”
Section: Results Of Using Against Cin Clinical Trials (Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…NAC positive on humans [53][54][55][56][57][58]60], meta-analyses [59,61,71] no results on humans [62][63][64][65][66][67], meta-analyses [68,69,72] Glutathione no results on humans [78][79][80] Vitamin C positive on humans [96][97][98], meta-analyses [94,95] no results on humans [99][100][101][102][103][104] Vitamin E positive on humans, meta-analyses [113,114] no results on humans [115,116] Bilirubin/HO-1 positive (expected)…”
Section: Results Of Using Against Cin Clinical Trials (Studies)mentioning
confidence: 99%
“…However, there are some conflicting data on the effectiveness of ascorbic acid in reducing the development of CIN. A number of studies have shown the absence of a nephroprotective effect of ascorbic acid upon administration of contrast agents [ 99 , 100 , 101 , 102 , 103 ]. No effects of ascorbic acid and NAC on CIN in critical care patients were found in [ 104 ].…”
Section: Antioxidants Vs Contrast-induced Nephropathymentioning
confidence: 99%